LIQUID-LIQUID EXTRACTION, PRECONCENTRATION AND TRANSPORT STUDIES OF LANTHANUM (III) WITH CALIX [4] RESORCINARENE-HYDROXAMIC ACID (C4RAHA) - JAIN,VINOD. K. (Sociedad Chilena de Química, 2007)
A liquid-liquid extraction and preconcentration of lanthanum (III) with a calix[4]resorcinarene bearing eight hydroxamic acid groups (C4RAHA) is described. Its analytical properties were investigated, and showed high affinity and selectivity towards lanthanum (III) in the presence of large quantities of associated metal ions. Quantitative extraction of lanthanum (III) with C4RAHA was achieved in ethyl acetate in the pH range 7.5-8.0. The extract is directly aspirated into ICP-AES, which increases the sensitivity and detection limit many folds. The λmax and molar absorptivity (ε) for lanthanum were 364nm and 8374 L mol-1cm-¹. The binding ratio of lanthanum with C4RAHA as evaluated by Jobs method is 4:1. The system obeys Beers law over the range 0.2 - 9.0 µg mL-¹ of lanthanum with Sandells sensitivity of 0.016 µg cm-². The preconcentration factor and overall two-phase stability constant evaluated at 25°C were 115 and 16.77 respectively. The complexation is characterized by favorable enthalpy and entropy changes. A liquid membrane transport study of lanthanum was carried out in a three-phase system under controlled conditions and a mechanism of transport is proposed. To ascertain the validity of the proposed method lanthanum has been determined in monazite sand and some standard geological standards